Effect of Tulsi (Ocimum sanctum) Leaf and Synbiotic Powder on Growth Performance, Nutrient Utilization, Carcass and Blood Biochemical Parameters in Broilers - Kohri, A.; Shende, K. A.; Dhuria, R. K.; Goklaney, D. (Indian Journal of Animal Nutrition, 2022)
A six-week feeding trial was followed by a metabolic trial using 120 broiler chicks (Cob-400) in a completely randomized block design to assess the effect of dietary supplementation with tulsi leaf and synbiotic powder as feed additives on growth performance of broilers. The four dietary treatments were designated as TC control group (basal diet), T1 supplemented with tulsi @ 0.5%, T2 supplemented with synbiotic @ 0.05%, T3 supplemented with tulsi @ 0.5% and synbiotic @ 0.05% of feed. Growth performance and carcass yields were significantly higher (P